Ekspresi karya seni visual anak anak gelandangan di Sekolah Bimbingan Jalinan Kasih (SBJK), Kuala Lumpur - Nafisah Md Noor (Tanjong Malim, 2020)
Ekspresi karya seni visual anak anak gelandangan di Sekolah Bimbingan Jalinan Kasih (SBJK), Kuala Lumpur by Nafisah Md Noor